Reporting of Medical Research Costs - Visser, B. J.; Buijink, A. W. G; Grobusch, M. P. (Methods of Information in Medicine, 2014)
Increasing numbers of research reporting guidelines are being published. These guidelines facilitate rigorous and complete reporting, and presentation of published studies. However, current reporting guidelines do not address issues related to costs of research methods. We propose to publish costs of research in order to increase transparency, efficiency, quality and ultimately reproducibility of scientific studies.
Keywords: Evidence-based medicine; research costs; publishing guidelines; transparency